TYPES OF PHOTOVOLTAIC CELLS AND THEIR EFFICIENCY - Yusupov Abdurashid Khamidillaevich; Oripova Dilnoza Karimjon kizi (World Scientific Research Journal, 2025)
Abstract: The efficiency of photovoltaic cells is determined by the factors that convert sunlight into electrical energy. This, in turn, depends on the materials of the photovoltaic cells, their production technologies, and the angle at which the photovoltaic cells are installed to receive sunlight. This work discusses the types of photovoltaic cells, their operating principles, and methods for increasing their efficiency.